Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 1 - Functions - 1.1 Review of Functions - 1.1 Exercises: 49

Answer

$f(x) = x -3 $

Work Step by Step

$(f ∘ g)(x) = x^2$ $g(x)=x^2+3$ $(f ∘ g)(x) = f(g(x)) = f(x^2+3) = x^2$ Therefore lets choose $f(x) = x -3 $ $(f ∘ g)(x) = f(g(x)) = f(x^2+3) =(x^2+3) -3= x^2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.